Tingkat Pencemaran Air Sungai Batanghari di Desa Teluk Rendah Pasar dan Desa Tuo Ilir Kecamatan Tebo Ilir Provinsi Jamb - Kurniawan, Hafiz Muchti (Universitasdiwangsa Jambi, 2020)
The Batang Hari river at both the region of Teluk Rendah Pasar and the village of Desa Tuo Ilir is theplace where half of community do their activity. The river is used by community not only as a source ofdrinking, bathing, and washing clothes but also as a landfill and human waste. The condition of the riverhas currently been predicted experiencing derivation in quality, this is caused by various human activitiesthat occur alongside the river. The quality of the water will be examinated by purposive random sampling which is at 2 station, (station 1 ) adge point 1 at the village of Teluk Rendah Pasar (station 1) middle point 1 at the village of Teluk Rendah Pasar and (station 2) adge point 2 at the village of Tuo Ilir (station 2) middle point 2 at the Village of Tuo Ilir subdistrict Tebo Ilir regency Tebo is the place of sampling. The results of parameter observation of DO, BOD, COD, and Hg. Quality of river water has beenpolluted with low pollution status. As a way to maintain quality of river water to be constant at its naturalcondition required controlling strategies of water pollution.